Evaluation of Risk Management Capability of Public-Sector Participants in Build-Operate-Transfer Highway Projects in Nigeria - Fabi, J.K.; Hamid, R.A; Mustapa, M; Mustapa, F.D (International Journal of Engineering and Technology, 2018)
Risks are inherent in BOT highway projects and have serious impact on its delivery. This paper seeks to evaluate the risk management capability of the public-sector participants involved in the execution BOT highway projects in Nigeria. Questionnaire survey was adopted to elicit information from experts who are active stakeholders in BOT highway construction in Nigeria. The population of the study comprises of government officials, contractors, concessionaires, bankers, consultant engineers and quantity surveyors, and academics. The study adopted stratified random sampling. Seventy-two (72) responses were obtained from One hundred and ten â€œ110â€ questionnaires administered. The study adopted fuzzy synthetic evaluation (FSE) method in the analysis of data because of its ability to handle multi attributes and multi criteria nature of the problems. The result indicated that their risk management capability is below average, though not too poor. It was found that low awareness of risk management and its importance is responsible for low overall risk management capability of the public sector and this has hindered efficient and effective project delivery by the public-sector participants. The study concluded that there is need for public-sector participants to give more attention to risk management practice and application, embrace formal risk management with considerable training to further improve their risk management capability.Â Evaluation of Risk Management Capability of Public-Sector Participants in Build-Operate-Transfer Highway Projects in Nigeria